Peningkatan Keterampilan Bermain Sape’ Melalui Metode Demonstrasi Pada Siswa-Siswi Kelas VII G SMPN 5 Pontianak - jian, Julianus; Olendo, Yudhistira Oscar; Muniir, Asfar (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research was motivated by the students' practice scores on the technical material for playing the Sape' musical instrument in class VII G SMPN 5 PONTIANAK under the minimum completeness criterion of 75%.